2019
DOI: 10.33206/mjss.465038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gastronomy Knowledge and Perception of Tourist Guides on Intention of Recommendation

Abstract: Bir bölgenin doğal, tarihi, kültürel yapısını ve gastronomisini turiste tanıtacak olan kişi genellikle turist rehberidir. Turist rehberleri turlarda turistlerin farklı destinasyonları ziyareti, eğlenme, yeni bilgiler edinme ve yeme-içme deneyiminde önemli rol oynamaktadır. Buradan hareketle, araştırmanın amacı, turist rehberlerinin gastronomi bilgisi ve turist rehberlerinin gastronomi turizmi algılarının tavsiye niyeti üzerine etkisini tespit etmektir. Araştırmanın amacı doğrultusunda 3 tane değişkeni içeren b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
5
0
2
Order By: Relevance
“…They therefore suggest that gastronomy should be incorporated into tourism curricula. Similarly, Akay & Özöğütçü (2019) revealed that the majority of tour guides have no training or education in cuisine, so their knowledge is rooted in books, magazines, TV programs, and online resources. They recommended that tour guides wishing to specialize in gastronomy tourism have a good command of the local culinary culture and practices in their destinations and be able to convey such information to tourists in detail.…”
Section: Guided Gastronomy Toursmentioning
confidence: 99%
See 2 more Smart Citations
“…They therefore suggest that gastronomy should be incorporated into tourism curricula. Similarly, Akay & Özöğütçü (2019) revealed that the majority of tour guides have no training or education in cuisine, so their knowledge is rooted in books, magazines, TV programs, and online resources. They recommended that tour guides wishing to specialize in gastronomy tourism have a good command of the local culinary culture and practices in their destinations and be able to convey such information to tourists in detail.…”
Section: Guided Gastronomy Toursmentioning
confidence: 99%
“…A number of researchers have studied tourist guiding and gastronomic tourism, such as from the perspective of tourist guides (Altıntaş & Hazarhun, 2020;Cankül & Yalçınkaya, 2021;İrigüler & Güler, 2015;Sahoo, 2020). Other studies have investigated specialization in gastronomy conceptually (Başoda etc., 2018), perceptions of students studying tourist guiding in gastronomy tours (Kök et al, 2021), the effect of tourist guides' gastronomic information on tourists' recommendation intentions (Akay & Özöğütçü, 2019), and tourists' perceptions of professional tourist guides in gastronomy tours (Seyitoğlu, 2020). İrigüler & Güler (2015) note that not enough tourist guides currently specialize in gastronomy tours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeterli bilgi ve donanıma sahip rehberler tarafından yönetilen, yerel mutfak kültürüne yönelik deneyimlere odaklı ve daha az destinasyonu içeren tur programları gastronomik deneyimler yaşamak isteyen turistler için giderek önem kazanmaktadır (Kızılırmak vd., 2016: 259). Akay & Özöğütçü (2019), turist rehberleri üzerinde yaptıkları araştırmada, çoğunluğunun mutfak konusunda eğitim almadığını, kitaplar, dergiler, TV programları ve internet kaynakları ile bilgilere ulaştıklarını ortaya koymuştur. Turist rehberleri, turistlerin seyahatleri boyunca ziyaret ettikleri yerlerdeki yerel lezzetler hakkındaki bilgiler ve yerel yiyecek-içeceklerin sunumunun o yöreye özgü bir şekilde yapılması açısından, turistlerin üzerinde güven unsuru oluşturmaktadır.…”
Section: Gastronomi Turizminde Rehberlik Ve Gelişme Perspektifleriunclassified
“…Özellikle Gastronomi Rehberliği ile ilgili yapılan çalışmaların ve eğitimlerin ülkemizin gelecekte gastronomi alanında çok önemli yerlere gelmesine büyük fayda sağlayacağı düşünülmektedir. Literatür incelendiğinde turist rehberliği ve gastronomi rehberliği kavramı ile ilgili çok az sayıda çalışma (Irigüler & Güler, 2015;Başoda vd., 2018;Akay & Özöğütçü, 2019;Akyurt Kurnaz & Kurnaz, 2019) olduğu görülmüştür. Gastronomi rehberliğinin giderek daha fazla önem kazanacağı düşünüldüğünde, turizm rehberliği eğitimi alan veya almakta olan kişilerin bu kavrama bakış açılarının ölçülmesinin literatüre katkı sağlayacağı ve araştırmadan elde edilecek bulguların değerlendirilmesinin turizmin gelişmesine önemli faydaları olabileceği öngörülmüştür.…”
Section: Introductionunclassified